2,6-Dichloro-7-isopropyl-7H-purine - Nikola Hloušková; Michal Rouchal; Marek Nečas; Robert Vícha (Acta Crystallographica Section E, 2012)
In the title molecule, C8H8Cl2N4, the essentially planar imidazole and pyrimidine rings [maximum deviations of 0.0030 (15) and 0.0111 (15) Å, respectively] make a dihedral angle of 1.32 (8)°. In the crystal, the fused-ring systems are stacked approximately parallel to the bc plane, with a centroid–centroid distance between inversion-related pyrimidine rings of 3.5189 (9) Å.